The effects of drug market regulation on pharmaceutical prices in Europe: Overview and evidence from the market of ACE inhibitors - Fritz von der Schulenburg; Sotiris Vandoros; Panos Kanavos (Health Economics Review, 2011)
This study provides an overview of policy measures targeting pharmaceutical expenditure in Europe and analyses their impact on originator pharmaceutical prices. Panel data methods are used to examine the market of ACE Inhibitors in six European countries (Denmark, France, Germany, Netherlands, Sweden, United Kingdom) over period 1991-2006. We find that although some measures are effective in reducing originator prices, others appear to have an insignificant effect. Results suggest that supply side measures such as mandatory generic substitution, regressive pharmacy mark-ups and claw-backs are effective in reducing pharmaceuticals prices. Results are not as strong for demand side measures. Profit controls and the use of cost-effectiveness analysis appear to have a negative effect on prices, while results on reference pricing are inconclusive. Findings also indicate that, although originator prices are not immediately affected by generic entry, they may be influenced by changes in generic prices post patent expiry.
Keywords: 330; regulation; pharmaceuticals; panel data; Europe; Pharmazeutisches Produkt; Preisregulierung; Gesundheitskosten; Europa